PO-31 - Circulating tumour cells and hypercoagulability: a lethal relationship in metastatic breast cancer. Issue 140 (April 2016) - Kirwan, C.C.; Clarke, A.C.; Howell, S.J.; Castle, J.
Abstract : Introduction: Circulating tumour cells (CTCs) are a marker of poor prognosis and are associated with increased risk of venous thromboembolism in metastatic breast cancer. Aim: We aimed to correlate presence of CTCs and markers of hyper-coagulability (D-dimer, fibrinogen and thrombin-antithrombin [TAT]) with survival in metastatic breast cancer. Materials and Methods: In a prospective study, enumeration of CTCs (CellSearch) and D-dimer, fibrinogen and TAT (ELISA) were measured at a single timepoint in 50 MBC (median age 59, range 36-82) patients undergoing active treatment. Survival data was determined at a median follow-up of 366 days (range 58-986). Results: To date, 25 patients have died (median survival 566 days, range 135-978). CTCs (> 1/7.5 ml) were identified in 13 patients (range 2-31) and were associated with increased markers of hypercoagulability [D-dimer: median 1814 (IQR 2700) vs 755 (IQR 735) ng/ml, p = 0.004; fibrinogen: median 4.2 (IQR 1.9) vs 3.2 (1.3) g/l, p = 0.05; TAT: median 6.2(IQR 6.3) vs 4.7 (5.2) ng/ml, p = 0.1]. CTCs were associated with visceral compared to just bony metastases (p = 0.03) and their presence was associated with a trend for reduced survival (295 days (CI: 0-652) vs 737 days (CI: 186-1288), p = 0.1). There was no correlation between CTCs /markers of hypercoagulability and age, oestrogen receptor, progesterone receptor or Her2 status. D-dimer, fibrinogen and TAT all inversely correlated with survival and were all significantly higher in patients dying within 1 year (D-dimer: 1098 (IQR 1122) vs 723 (IQR 735) ng/ml, p = 0.03; fibrinogen: 4.4 (1.1) vs 3.2 (0.8) g/l, p = 0.004; TAT: 8.1 (6.3) vs 4.7(3.1) ng/ml, p = 0.03 [analysis excludes patients with < 1 year follow-up, n = 13]). D-dimer > 1, 500 ng/ml was associated with significantly reduced survival (295 days [CI: 0-615] vs 836 days [404-1267], p = 0.05). On Cox regression, D-dimer, but not fibrinogen or TAT was associated with an increased risk of death (HR 1.3 per 1, 000 ng/ml D-dimer, p = 0.07). Conclusions: The correlation between CTCs, hypercoagulability and reduced survival in metastatic breast cancer suggests a possible role for the coagulation system in supporting tumour cell metastasis and is therefore a potential therapeutic target.